Reviewer Acknowledgements for Environmental Management and Sustainable Development, Vol. 10 No. 4 - Young, Jenny (Environmental Management and Sustainable Development, 2021)
Environmental Management and Sustainable Development (EMSD) would like to thank the following reviewers for reviewing manuscripts from August 1, 2021, to November 1, 2021. Their comments and suggestions were of great help to the authors in improving the quality of their papers. Many authors, regardless of whether EMSD publishes their work, appreciate the helpful feedback provided by the reviewers. Macrothink Institute appreciates the following reviewers’ rigorous and conscientious efforts for this journal. Each of the reviewers listed below returned at least one review during this period. Aristotulus Ernst Tungka, University of Sam Ratulangi Manado, Indonesia Christiane do Nascimento Monte, Universidade Federal Fluminense, Brazil Chuck Chuan Ng, Xiamen University Malaysia, Malaysia Dastun Gabriel Msuya, Sokoine University Of Agriculture, Tanzania Hayssam Mohamed Ali, King Saud University, Egypt João Fernando Pereira Gomes, Instituto Superior de Engenharia de Lisboa, Portuguese Nuralam Hossain, Chongqing University, China Oylum Gokkurt Baki, Sinop University, Turkey Pankaj Maheshwari, College of Engineering, University of Nevada, Las Vegas, USA Tateda Masafumi, Toyama Prefectural University, Japan